2008
DOI: 10.1088/1475-7516/2008/11/008
|View full text |Cite
|
Sign up to set email alerts
|

Palatini versus metric formulation in higher-curvature gravity

Abstract: We compare the metric and the Palatini formalism to obtain the Einstein equations in the presence of higher-order curvature corrections that consist of contractions of the Riemann tensor, but not of its derivatives. We find that there is a class of theories for which the two formalisms are equivalent. This class contains the Palatini version of Lovelock theory, but also more Lagrangians that are not Lovelock, but respect certain symmetries. For the general case, we find that imposing the Levi-Civita connection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(119 citation statements)
references
References 32 publications
2
117
0
Order By: Relevance
“…Indeed, whereas the gauge and the Palatini formalisms are found to be equivalent by requiring the presence of a metric-compatible connection [22], it is shown that the latter also implies the metric formalism but the opposite is not true for theories endowed with this type of higher order curvature corrections in the Lagrangian [23].…”
Section: Solutions Of the Eym-lorentz Ansatzmentioning
confidence: 98%
“…Indeed, whereas the gauge and the Palatini formalisms are found to be equivalent by requiring the presence of a metric-compatible connection [22], it is shown that the latter also implies the metric formalism but the opposite is not true for theories endowed with this type of higher order curvature corrections in the Lagrangian [23].…”
Section: Solutions Of the Eym-lorentz Ansatzmentioning
confidence: 98%
“…This very setup, the so-called Palatini formulation or first-order formalism, does not necessarily admit the Levi-Civita connection if the matter sector depends explicitly on the affine connection [14,15]. In this formalism, connection and metric are independent geometrodynamical variables [16], and this very fact has physically interesting consequences for inflation [16][17][18][19][20][21] as well as other phenomena like the cosmological constant problem [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…ρσ term was already established in literature [8,34]. And now we will calculate the actual difference at the level of solutions, expanding the equations in powers of λ.…”
Section: The Fact That F1 and F2 Versions Of Einstein Equation Differmentioning
confidence: 97%
“…There are known few more theories which exhibit such equivalence [7,8], but for an arbitrary gravity theory the equivalence is generally broken. Identically looking actions provide different equations of motion in F1 and F2 approaches [9].…”
Section: Introductionmentioning
confidence: 99%